Social Attention in a Virtual Public Speaking Task in Higher Functioning Children with Autism - Jarrold, William (2013)
BACKGROUND: Impairments in social attention play a major role in autism, but little is known about their role in development after preschool. In this study a public speaking task was used to study social attention, its moderators, and its association with classroom learning in elementary and secondary students with higher functioning Autism Spectrum Disorder (HFASD). METHOD: Thirty-seven students with HFASD and 54 age and IQ-matched peers without symptoms of ASD were assessed in a virtual classroom public speaking paradigm. This paradigm assessed the ability to attend to 9 avatar peers seated at a table, while simultaneously answering self-referenced questions. RESULTS: Students with HFASD looked less frequently to avatar peers in the classroom while talking. However, social attention was moderated in the HFASD sample such that students with lower IQ, and/or more symptoms of social anxiety, and/or more ADHD Inattentive symptoms, displayed more atypical social attention. Group differences were more pronounced when the classroom contained social avatars versus non-social targets. Moreover, measures of social attention rather than non-social attention were significantly associated with parent report and objective measures of learning in the classroom. CONCLUSIONS: The data in this study supports the hypothesis of the Social Attention Model of ASD that social attention disturbance remains part of the school-aged phenotype of autism that is related to syndrome specific problems in social learning. More research of this kind would likely contribute to advances in the understanding of the development of autism and educational intervention approaches for affected school-aged children.